Treatment of acute sore throat in Malaysia: a consensus of multidisciplinary recommendations using modified Delphi methodology - Abdullah, Baharudin; Koh, Kar Chai; Mohamed, Mohazmi; Tan, Vincent Eng Soon; Mohammad, Nurashikin; Sekawi, Zamberi; Periyasamy, Petrick; Ramadas, Anitha; Duerden, Martin (Dove Medical Press, 2024)
Introduction: Using antibiotics in the treatment of acute sore throats has been linked with antimicrobial resistance (AMR) and needs to be addressed. The consensus sought to improve diagnostic accuracy, decrease unwarranted antibiotic prescriptions and enhance patient outcomes. Methods: A multidisciplinary panel of nine experts reviewed published literature and discussed current practices in managing sore throat. Ten evidence-based statements on sore throat and AMR, diagnostic accuracy and antibiotic prescribing, and symptomatic therapy were developed. A modified Delphi exercise was then carried out. A consensus was reached if at least 70% of the group agreed with the statement. Results: All 10 statements for managing acute sore throat achieved consensus. The major concern of AMR caused by improper antibiotic prescribing, particularly in cases of viral sore throat, was recognized. This underscores the need for improved diagnostic tools, such as the McIsaac score, to reduce needless antibiotic prescriptions. To improve patient satisfaction, effective pain management using non-antibiotic alternatives such as paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs), and flurbiprofen throat lozenges was recommended. Pain and inflammation can be adequately managed with low-dose NSAIDs. The potential benefits of topical NSAIDs were acknowledged for their milder safety profile than oral formulations. Conclusion: A consensus was achieved on the use of a clinical diagnostic tool, prudent use of antibiotics, and symptomatic therapy in acute sore throat management. The McIsaac score and point-of-care testing (POCT) for the presence of group A beta-hemolytic Streptococcus (GABHS) can aid in the decision-making process for antibiotic use, reducing needless prescriptions. The mainstay of therapy is symptomatic treatment, which includes the use of NSAIDs.